2021
DOI: 10.1249/mss.0000000000002809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concurrent Training on Body Composition and Gut Microbiota in Postmenopausal Women with Overweight or Obesity

Abstract: Purpose: Menopause tends to be associated with an increased risk of obesity and abdominal fat mass (FM) and is associated with lower intestinal species diversity. The aim of this study was to determine the effects of a high-intensity interval training and resistance training (HIIT + RT) program on body composition and intestinal microbiota composition in overweight or obese postmenopausal women. Methods: Participants (n = 17) were randomized in two groups: HIIT + RT group (3  / week, 12 weeks) and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 57 publications
3
50
0
Order By: Relevance
“…Likewise, a study showed that high-intensity interval training and resistance work modified the composition of the intestinal microbiota [ 77 ]. Regarding resistance work, it is capable of modestly modifying the microbiota composition and function compared to other types of exercise [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a study showed that high-intensity interval training and resistance work modified the composition of the intestinal microbiota [ 77 ]. Regarding resistance work, it is capable of modestly modifying the microbiota composition and function compared to other types of exercise [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may also improve glucose metabolism [ 184 , 185 , 186 ]. Furthermore, HIIT modulates gut microbiota composition in humans and rodents [ 112 , 113 , 114 , 115 , 187 ]. A growing body of evidence suggests that in humans, dietary interventions, including supplementation of creatine monohydrate, caffeine, nitrate, sodium bicarbonate, beta-alanine, proteins, and essential amino acids, as well as manipulating carbohydrate availability, lead to more favorable outcomes after HITT programs by enhancing energy metabolism or by increasing the adaptive response during recovery [ 167 ].…”
Section: Gut Microbiota Modulation By Exercise and Nutrition For Heal...mentioning
confidence: 99%
“…The gut microbiome has been correlated with menopause: the cessation of menstruation accompanied by estrogen down-regulation, ovary function loss, and hormone receptors dysfunction [ 16 , 38 ]. Menopause is associated with a lower gut microbial species diversity [ 92 ]. Thus, there are marked differences in the gut microbiomes and their metabolites in premenopausal and postmenopausal women, as shown in Table 1 and Figure 1 [ 93 ].…”
Section: Gut Microbiota Composition Alterations Accompanying Menopausementioning
confidence: 99%
“…Obesity affects 65% of postmenopausal women and interestingly, the relationship between the gut microbiota and estrogen is speculated to mediate this weight gain [ 16 ]. Moreover, the gut microbiome has been related to obesity, and menopause is associated with a heightened risk of obesity [ 92 , 93 ]. Notably, other than the differences in Akkermansia muciniphila , Bifidobacterium animalis, Dorea, and Desulfovibrio, the gut microbial characteristics of diet-induced and bilaterally ovariectomized obese mice are reportedly similar [ 38 ].…”
Section: The Role Of the Gut Microbiome In Postmenopausal Female Healthmentioning
confidence: 99%